A POET WITH A SINCERE HEART - Sobirova, Asilabonu Aziz kizi (Educational Research in Universal Sciences, 2023)
This article gives information about a skillful artist Alexander Arkadevich Feinberg who can depict his feelings towards Uzbekistan and worked side by side with Uzbek people throughout his life. While reading this article, you can learn about his literary and translation works. He made a great contribution to the development of the country with his indelible heritage.